Birth and growth - Burgess, Janet, 1952- (UK : Longmans, 1989)
Explains how babies are born, grow, become children, then adults, and eventually die.
Includes index.
Keywords: Human growth -- Juvenile literature; Childbirth -- Juvenile literature; Developmental biology -- Juvenile literature; Growth